Normative arguments from experts and peers reduce delay discounting - Nicole Senecal; Teresa Wang; Elizabeth Thompson; Joseph W. Kable (Judgment and Decision Making, 2012)
When making decisions that involve tradeoffs between the quality and timing of desirable outcomes, people consistently discount the value of future outcomes. A puzzling finding regarding such decisions is the extremely high rate at which people discount future monetary outcomes. Most economists would argue that decision-makers should turn down only rates of return that are lower than those available to them elsewhere. Yet the vast majority of studies find discount rates that are significantly higher than market interest rates (Frederick et al., 2002). Here we ask whether a lack of knowledge about the normative strategy can explain high discount rates. In an initial experiment, nearly half of subjects did not spontaneously cite elements of the normative strategy when asked how people should make intertemporal monetary decisions. In two follow-up experiments, after subjects read a ``financial guide'' detailing the normative strategy, discount rates declined by up to 85%, but were still higher than market interest rates. This decline persisted, though attenuated, for at least one month. In a final experiment, peer-generated advice influenced discount rates in a similar manner to ``expert'' advice, and arguments focusing on normative considerations were at least as effective as others. These studies show that part of the explanation for high discount rates is a lack of knowledge regarding the normative strategy, and they quantify how much discount rates are reduced in response to normative arguments. Given the high level of discounting that remains, however, there are other contributing factors to high discount rates that remain to be quantified.